Preparação e avaliação de catalisador heterogêneo ácido baseado em óxido de grafeno funcionalizado para síntese de biodiesel - SILVA, Paula Maria Melo da (Universidade Federal do Pará, 2025)
The present study aims at the synthesis of a heterogeneous acid catalyst derived from graphene oxide, applied in the transesterification reaction of soybean oil to obtain biodiesel. The graphene oxide catalytic support was synthesized from graphite oxidation and the catalyst was functionalized by impregnation of molybdenum trioxide (MoO3) as the active phase. The synthesis of the support and the catalyst was confirmed through the characterization techniques of Fourier Transform Infrared Spectroscopy (FT-IR), Thermogravimetric Analysis (TG/DTG), Scanning Electron Microscopy (SEM), Energy Dispersion X-Ray Spectroscopy (EDS) and XRay Diffraction (DRX). The catalytic tests optimization of the transesterification reactions had as parameters evaluated the temperature in the range of 120–160 °C, the time between 1–5 h, the catalyst concentration comprised in 10% (m/m) and molar ratio oil/ alcohol in the range of 25:1–45:1. The reaction studies evidenced as an optimum point the temperature of 140 °C, time of 5 h, catalyst concentration 6% (m/m) and molar ratio of 35:1, leading to the obtainment of a biodiesel with an ester content above 90%. The catalyst also maintained its catalytic activity even in the seventh reaction cycle. Therefore, the results obtained demonstrate that the graphene oxide catalyst supported by MoO3 is a new and promising heterogeneous acid catalyst with high catalytic efficiency in the transesterification reaction for the biodiesel synthesis.